Experience with the use of a partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft - Birk, Stephanie; Brase, Christoph; Hornung, Joachim (Otology & Neurotology, 2014)
In the further development of alloplastic prostheses for use in middle ear surgery, the Dresden and Cologne University Hospitals, working together with a company, introduced a new partial ossicular replacement prosthesis in 2011. The ball-and-socket joint between the prosthesis and the shaft mimics the natural articulations between the malleus and incus and between the incus and stapes, allowing reaction to movements of the tympanic membrane graft, particularly during the healing process.Retrospective evaluationTo reconstruct sound conduction as part of a type III tympanoplasty, partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft was implanted in 60 patients, with other standard partial ossicular replacement prosthesis implanted in 40 patients and 64 patients. Pure-tone audiometry was carried out, on average, 19 and 213 days after surgery. Results of the partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft were compared with those of the standard prostheses.Early measurements showed a mean improvement of 3.3 dB in the air-bone gap (ABG) with the partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft, giving similar results than the standard implants (6.6 and 6.0 dB, respectively), but the differences were not statistically significant. Later measurements showed a statistically significant improvement in the mean ABG, 11.5 dB, compared with 4.4 dB for one of the standard partial ossicular replacement prosthesis and a tendency of better results to 6.9 dB of the other standard prosthesis.In our patients, we achieved similarly good audiometric results to those already published for the partial ossicular replacement prosthesis with a ball-and-socket joint between the plate and the shaft. Intraoperative fixation posed no problems, and the postoperative complication rate was low.
EVALuna2:19989